Pengetahuan tentang osteoporosis yang rendah menurunkan konsumsi susu pada murid SMA - Intan Aru Palaka; Adi Hidayat (Fakultas Kedokteran Universitas Trisakti, 2018)
BACKROUND Milk is also a main source of calcium and phospor that very important for bone formation. Milk is very good to consumed for adolesence, because there’s bone tissue development that was a preparation phase to reach the top of bone mass growth while on adolesence stage. Osteoporosis is a disease that can be marked with poor bone mass and decline the structure of bone tissue, that can lead to vulnerability of bone and increase the risk of fracture. This research aims to determine the relationship between knowledge of osteoporosis and milk consumption in senior high school students. METHODS This study was used an analytic observational with a cross-sectional design that was conducted from July to October 2017. Samples was took with cluster sampling and simple random sampling in 182 respondent in SMA Negeri 2 Mejayan. Data were collected using an osteoporosis knowledge questionnaire and a questionnaire of milk consumption behavior.The data were analyzed with Chi-Square test RESULTS Subjects with knowledge of low osteoporosis, 27 (50.0%) did not drink milk significantly higher than subjects with high osteoporosis knowledge of 5 people (3.9%). The analysis result based on Chi-Square test showed that there was a significant relationship between knowledge of osteoporosis and milk consumption in senior high school students (p = 0.000). CONCLUSION This study showed that there was a significant correlation between knowledge of osteoporosis and milk consumption insenior high school students.